Pengaruh Pengaruh Faktor-Faktor Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Pada Kantor Pemerintah Daerah Kabupaten Karimun - Roli Sambuardi; Fauzan Haqiqi; Azmi (Bahasa Indonesia, 2020)
This research was conducted with the object of the Regional Government Office of Karimun Regency, involving respondents who were employees of the Regional Government Office of Karimun Regency, amounting to 37 people. The purpose of this study was to analyze the effect of organizational culture values ​​both simultaneously and partially on the level of job satisfaction of employees of the Regional Government Office of Karimun Regency. Besides that, there is the most dominant variable influencing employee job satisfaction. The variables in this study include eight independent variables consisting of the Principle of Purpose, Principle of Excellence, Principle of Consensus, Principle of Unity, Principle of Achievement, Principle of Empiricism, Principle of Familiarity, Principle of Integrity, and one dependent variable namely employee job satisfaction. Hypothesis testing results in that the principle of integrity has the most dominant influence on job satisfaction of Karimun Regency Government Office Employees. This is indicated by the tcount value of 6,521 with a significance level of 0,000 greater than the table of 2,045. This shows that there is a rejection of Ho and Ha acceptance, which means there is a significant influence of the integrity principle variable on the job satisfaction variable of the Employees of the Regional Government Office of Karimun Regency (Y). This t count value is stated to be the largest compared to the other variables.